The instrumental rationality of addiction. - Pickard, H (2011)
The claim that non-addictive drug use is instrumental must be distinguished from the claim that its desired ends are evolutionarily adaptive or easy to comprehend. Use can be instrumental without being adaptive or comprehensible. This clarification, together with additional data, suggests that Müller and Schumann's (MandS's) instrumental framework may explain addictive, as well as non-addictive consumption.